Validation of a treatment algorithm for orthopaedic implant-related infections with device-retention—results from a prospective observational cohort study. (May 2016) - Tschudin-Sutter, S.; Frei, R.; Dangel, M.; Jakob, M.; Balmelli, C.; Schaefer, D.J.; Weisser, M.; Elzi, L.; Battegay, M.; Widmer, A.F.
Abstract: Success rates for treatment regimens involving retention of an infected implant are conflicting and failure rates of up to 80% have been reported. We aimed to validate a proposed treatment algorithm, based on strict selection criteria, by assessing long-term outcome of treatment for orthopaedic device-related infection (ODRI) with retention. From January 1999 to December 2009, all patients diagnosed with ODRI at the University Hospital Basel, Switzerland were eligible for treatment with open surgical debridement, implant-retention and antibiotics, if duration of clinical symptoms was ≤3 weeks, the implant was stable, the soft-tissue had no abscess or sinus tract, and the causative pathogen was susceptible to antimicrobial agents with activity against surface-adhering microorganisms. Antimicrobial treatment was administered according to a predefined algorithm. The primary outcome was treatment failure after 2-year follow up. A total of 455 patients were diagnosed with an ODRI, of whom 233 (51.2%) patients were eligible for treatment involving implant-retention. Causative pathogens were mainly Staphylococcus aureus (41.6%) and coagulase-negative staphylococci (33.9%). Among patients with ODRIs related to prostheses, failure was documented in 10.8% (12/111) and in patients with ODRIs related to osteosyntheses, failure occurred in 9.8% (12/122) after 2 years of follow up. In all, 90% of ODRIs were successfully cured with surgical debridement and implant-retention in addition to long-term antimicrobial therapy according to a predefined treatment algorithm: if patients fulfilled strict selection criteria and there was susceptibility to rifampin for Gram-positive pathogens and ciprofloxacin for Gram-negative pathogens.